2011
DOI: 10.1186/1471-2407-11-49
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β-catenin and Akt pathways by Twist are critical for the maintenance of EMT associated cancer stem cell-like characters

Abstract: BackgroundEpithelial-mesenchymal transition (EMT) not only confers tumor cells with a distinct advantage for metastatic dissemination, but also it provides those cells with cancer stem cell-like characters for proliferation and drug resistance. However, the molecular mechanism for maintenance of these stem cell-like traits remains unclear.MethodsIn this study, we induced EMT in breast cancer MCF7 and cervical cancer Hela cells with expression of Twist, a key transcriptional factor of EMT. The morphological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
235
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(252 citation statements)
references
References 35 publications
12
235
0
Order By: Relevance
“…It was generally believed that ROS exert cytotoxic and genotoxic effects by causing damage to lipids, proteins and DNA, because of their greater chemical reactivity with regard to oxygen [15,21]. Recently, however, ROS was proposed to be involved in tumor metastasis as a second-messenger for regulation of diverse cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was generally believed that ROS exert cytotoxic and genotoxic effects by causing damage to lipids, proteins and DNA, because of their greater chemical reactivity with regard to oxygen [15,21]. Recently, however, ROS was proposed to be involved in tumor metastasis as a second-messenger for regulation of diverse cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that both Akt/mTOR and STAT-3 pathways were upstream pathways controlling both EMT and expression of MMP-2 and MMP-9 [15][16][17][18]. Therefore, we wanted to determine whether PI3K/Akt and STAT-3 pathways were activated upon low-concentration capsaicin treatment.…”
Section: Low-concentration Capsaicin Promotes Migration and Invasionmentioning
confidence: 99%
“…Twist1 expression downregulates E-cadherin, but upregulates the EMT markers CD44, Slug (also known as SNAI2) and Snail Li and Zhou, 2011;Casas et al, 2011). Thus, we initially tested their promoter activities using the corresponding luciferase plasmids.…”
Section: Aurka and Twist1 In Emtmentioning
confidence: 99%
“…23 It has been reported that HIF-1 promotes EMT through direct regulation of EMT-related proteins, such as TWIST. 24 During EMT process, epithelial cell layers lose polarity together with cell-to-cell contacts. The expression of proteins that promote cell-to-cell contact, such as E-cadherin, may be lost, and the cells may acquire mesenchymal markers such as vimentin and the MMPs MMP-9, resulting in an enhanced ability for cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%